The phenomenon of contradiction in Khurshid Davron's poetry and its significance in linguistics - Kurbanova Muharram Jurabekovna (Genius Journals, 2022)
Explains the elements of language in Uzbek linguistics, syntactic figures and their importance in the literature. At the same time, the interdependence of language and literature is analyzed.
Keywords: Antithesis; contrast; antonym; lingvopoetics